Contribution of Agroforestry to Economy, Livelihood and Environment in India: Reminisces of a Life Time between 1957-2008 - Tejwani, K.G. (Indian Journal of Agroforestry, 2020)
Indian Council of Agricultural Research (ICAR) has developed a vast network of AF research: 36 centers in all agro-climatic zones. First approximation 257.559 million ha of land outside the "state" forest carry 15341.0 million tress on an average of 59 trees per ha. Agroforestry (outside the forest) has more number of trees (15341.0 million) than the "State" Forest (14905.7 million). It follows from the analysis that AF practiced by the farmers, planters, shifting cultivators, urban people has more trees than those in the "State" (Govt.) forests. This has many implications for the policy, Institutions and programmes of Forest (Govt.) Departments and towards AF practiced by the people outside the forests. This conclusion will also have implications for the economy, livelihood (of humans and livestock) and environment.